Autobiographical memory following weight gain in adult patients with anorexia nervosa: a longitudinal study - Terhoeven, Valentin; Faschingbauer, Sandra; Huber, Julia; Simon, Joe J.; Herzog, Wolfgang; Friederich, Hans-Christoph; Nikendei, Christoph (European eating disorders review, 2024)
Background Patients with anorexia nervosa (AN) show overgeneralization of memory (OGM) when generating autobiographical episodes related to food and body shape. These memories are central for the construction of a coherent self-concept, interpersonal relationships, and problem-solving abilities. The current study aims to investigate changes in autobiographical memory following weight gain. Methods OGM was assessed with an adapted version of the Autobiographical Memory Test including food-, body-, depression-related, and neutral cues. N = 41 female patients with AN (28 restricting-, 13 binge-eating/purging-subtype; mean disease duration: 4.5 years; mean BMI: 14.5 kg/m2) and N = 27 healthy controls (HC) were included at baseline. After inpatient treatment (mean duration: 11 weeks), 24 patients with AN and 24 age-matched HC were reassessed. Group differences were assessed using independent samples t-tests for cross-sectional comparisons and repeated measures ANOVAs for longitudinal data. Results At baseline, patients with AN generated significantly fewer specific memories than HC, independent of word category (F(1.66) = 27.167, p < 0.001). During inpatient stay, the average weight gain of patients with AN was 3.1 body mass index points. At follow-up, patients with AN showed a significant improvement in the number of specific memories for both depression-related and neutral cues, but not for food- and body-related cues. Conclusions Generalised OGM (i.e., independent of word category) in patients with AN before weight restoration may be a general incapacity to recall autobiographical memory. After weight gain, the previously well-studied pattern of eating disorder-related OGM emerges. The clinical relevance of the continuing disorder-related OGM in patients with AN after weight gain is discussed.